Pengaruh File Apk Terhadap Keamanan Sistem Operasi Android Berdasarkan Analisis Statik dan Dinamik - Riyadi, Tri Agus (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2022)
Many devices using Android such as handphone, tablet and others. Android makes the daily works become so easy to activate other devices using IoT technology. To use those facilitate, Android user should install a file such as an apk file. The objective of this research is to examine the impact of an apk file in Android using static and dynamic analysis. First, static analysis was done using Qark and the results are three recommendation such as vulnerable, warning and information. Second, dynamic analysis was done by giving the permission to the apk file when it was installed in Android. The impact of this condition was anyone could access almost all the resources in the Android such as SMS when connected to internet.